Teachers’ Perceptions on Problem-Based Learning Model in Teaching English: A Case Study at SMAN 2 Mataram in Academic Year 2023/2024 - Hadziq, Muhammad Bayin; Sahuddin; Nurtaat, Lalu; Nawawi, Nawawi; Amrullah (Journal of English Education Forum (JEEF), 2024)
This study investigates teachers’ perceptions on Problem-Based Learning (PBL) model in teaching English at State High School 2 Mataram or SMAN 2 Mataram. The research questions concern about what are the teachers’ perceptions of PBL, the challenges faced by English teachers in implementing PBL, and how teachers overcome the challenges teaching English. The researcher used questionnaire, interview, and document analysis to collect the data. The data was analyzed using three steps of qualitative data analysis; data reduction, data display, and conclusion drawing/verification. The findings suggest that teachers perceive PBL as an effective model for teaching English, fostering collaboration, critical thinking, and argumentation among students. However, they face challenges such as varying student comprehension levels and reliance on the internet for quick solutions. To overcome these challenges, teachers adopt approaches such as guiding students with low comprehension levels patiently and emphasizing the importance of in-depth research to deter reliance on instant internet solutions. The study contributes to the field of English language teaching by providing insights into the challenges and solutions related to PBL implementation.